Socialism and the Will to Fail A Critical Review of the Book Socialism: A Failed Idea That Never Dies - Morteza Bahrani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article is based on a review of Socialism: A Failed Idea That Never Dies (by Kristian Niemietz). Where Niemietz believes that the idea of socialism is still alive despite its successive failures, I will argue that the problem is not that the "ideas" are dead or alive. Human mental phenomena include ideas, judgments, and wills. Ideas never die; whether it is the idea of socialism or the idea of God or the Idea of the dragon. The main issue is the rightness or wrongness of human will. Accordingly, I have tried to show, in a critical phenomenological way, that socialism is a will to failure. If it is repeated and experienced a thousand more times, it will achieve nothing but failure. On the contrary, and by historical experience, it is capitalist liberalism that has set before us the right and progressive will. For those of us who have stepped forward in the process of progress, the moral imperative is to put aside the socialist temptations of equal distribution. The beginning of our progress is to step on the path of production. Production and exchange of capital are the other words of free exchange and the right to freedom. It is only with this right that we can achieve ourselves in this worldly world.